Violence in Youth Football. Sports or Socio-Cultural Phenomenon? - Jorge Delgado Di Biase (European Scientific Journal, ESJ, 2017)
Youth sport events are part of a growing industry to which event venues are tailoring their policies, procedures, and designs. The competitive nature of the events and their participants have caused these venues to examine their existing policies and adjust them to increase security and safety measures for the athletes, coaches, spectators, game officials, and venue staff. Tempers at these events will flare, and in recent years violence is becoming increasingly more common. Parents and athletes have attacked each other, coaches, and game officials due to the intense nature of these events. The result of these acts could range from minor injuries to death. In Montevideo and in all Uruguay, we are witnessing an escalation of violence that exists in all football training divisions. This aggressions are not only detected in the official encounters, inside and out of the courts. They are also seen daily in practices, youth complexes, where the subjects are prepared. My dual role in sport’sorganizations, as coach trainer of the technical bodies and sports psychologist at all educational levels, led me to observe and witness this phenomenon directly, achieving a practical study of the problem.